2019
DOI: 10.1029/2019ms001661
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in the Representation of Orography in Weather and Climate Models and Implications for Parameterized Drag

Abstract: The representation of orographic drag remains a major source of uncertainty for numerical weather prediction (NWP) and climate models. Its accuracy depends on contributions from both the model grid‐scale orography and the subgrid‐scale orography (SSO). Different models use different source orography data sets and different methodologies to derive these orography fields. This study presents the first comparison of orography fields across several operational global NWP models. It also investigates the sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…On the other hand, the blocked layer depth (Zb) is still able to scale with the subgrid mountain height. The sensitivity of the surface stress and gravity wave momentum flux to the σ and α fields used in global NWP models is demonstrated in Elvidge et al, (), and the transition of the gravity wave stress between subcritical (h<U/(NFc)) and supercritical (h(U/(NFc)) flow regimes is discussed and illustrated in their fig. c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the blocked layer depth (Zb) is still able to scale with the subgrid mountain height. The sensitivity of the surface stress and gravity wave momentum flux to the σ and α fields used in global NWP models is demonstrated in Elvidge et al, (), and the transition of the gravity wave stress between subcritical (h<U/(NFc)) and supercritical (h(U/(NFc)) flow regimes is discussed and illustrated in their fig. c.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the partitioning between the orographic and boundary layer drag is very different between the two models (Zadra et al, ; Sandu et al, ). These differences are likely a result of a combination of subjective tuning, differences in formulation and, as recently demonstrated by Elvidge et al, (), the representation of subgrid orographic fields. The implications of these differences between the UM's and the IFS's treatment of parametrised orographic drag for the total drag and its variability over the northern Rocky Mountains will be considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major findings of Elvidge et al . () is that the UM currently has smoother mean orography than other centres. Upcoming changes to the orography ancillary generation method (van Niekerk, personal communication [2019]) include a significant reduction in smoothing of both the resolved and sub‐grid orography fields, which should improve model representation of orographic volume for poorly resolved mountains, allowing for better representation of orographic drag and precipitation enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…Work is currently ongoing to investigate the reasons for excessive drag due to subgrid low-level orographic blocking, which has the effect of producing too much ascent and therefore precipitation upstream of major orography and not enough over the mountains themselves. One of the major findings of Elvidge et al (2019) is that the UM currently has smoother mean orography than other centres. Upcoming changes to the orography ancillary generation method (van Niekerk, personal communication [2019]) include a significant reduction in smoothing of both the resolved and sub-grid orography fields, which should improve model representation of orographic volume for poorly resolved mountains, allowing for better representation of orographic drag and precipitation enhancement.…”
Section: F I G U R E 19mentioning
confidence: 99%